Identification of potential therapeutic targets for Streptococcus suis infection - Jeffreys, Bethan (2021)
Streptococcus (S.) suis is a commensal porcine pathogen that is the leading causative agent of bacterial meningitis and sepsis in young pigs globally. Systemic infection in swine is associated with considerable mortality and has significant animal welfare and economic consequences. This zoonotic pathogen causes similar clinical pathology in humans as seen in pigs, which can result in life-changing post-streptococcal sequelae. S. suis is recognised as an emerging zoonotic disease and is the primary cause of meningitis in human adults in South East Asia, with two recent outbreaks in China manifesting as Streptococcal toxic shock-like syndrome in patients. The virulence mechanisms by which S. suis transitions from a commensal species within the nasopharynx and tonsillar microflora to a pathogenic species proliferating within host blood and disseminating into peripheral organs and the brain are still largely unknown. Proposed virulence mechanisms are often extrapolated from current knowledge about the pathogenesis of similar infections caused by Group A and Group B Streptococci. Whilst S. suis infections are readily treatable with β-lactam antibiotics, reports of antimicrobial resistance are increasing and driving the need for alternative therapeutics with novel targets and mechanisms of action. Maintaining effective treatment options are critical as the genetic diversity of serotypes within the S. suis strain population has meant that an effective commercial vaccine has yet to be developed. Establishing a more comprehensive understanding of the mechanisms of S. suis pathogenesis must be achieved to identify molecular targets for novel therapies and diagnostic tools.